Electronic structural studies of µ3-Sn(OR)3 capped trinuclear nickel clusters. (15th September 2022) - Torquato, Nicole A.; Lara, Jaden K.; Bertrand, Quentin C.; Mrse, Anthony A.; Gembicky, Milan; Kubiak, Clifford P.
Graphical abstract: Spectroscopic and structural comparisons are made between a series of (OR)3 Sn capped trinuclear nickel clusters. Abstract: Spectroscopic and structural comparisons are made between a series of (OR)3 Sn capped trinuclear nickel clusters. The synthesis of the (OEt)3 Sn and (OPh)3 Sn capped nickel clusters, [Ni3 (dppm)3 (μ3 -Cl)(μ3 -Sn(OEt)3 )] (1 ), [Ni3 (dppm)3 (μ3 -Cl)(μ3 -Sn(OPh)3 )] (2 ), was realized by the treatment of [Ni3 (dppm)3 (μ3 -Cl)(μ3 -SnCl3 ] with 6 eq. of KOEt or NaOPh, respectively. Treatment of complex 1 with 10 eq. glycerol results in the synthesis of the (C3 H5 O3 )Sn capped trinuclear nickel cluster, [Ni3 (dppm)3 (μ3 -Cl)(μ3 -Sn(C3 H5 O3 ))] (3 ). The crystallographic studies of these clusters allow a detailed structural comparison. In addition, cyclic voltammetric data were obtained for complexes 1, 2, and 3 and their electrochemical properties are compared. Complex 1 and 3 exhibit reversible oxidation and reduction events. Complex 2 displays a reversible oxidation and a pseudo-reversible reduction.